Answer:
The vertex form of this equation is y = (x + 3)^2 - 11
Step-by-step explanation:
In order to find the vertex form of the equation, we have to do a process called completing the square. The step by step instructions are below for you.
y = x^2 + 6x - 2
Add/Subtract the constant to the y side of the equation.
y + 2 = x^2 + 6x
Take half of the 6 coefficient (3) and then square it (9). Add that number to both sides.
y + 11 = x^2 + 6x + 9
Now you can factor the right side as a perfect square.
y + 11 = (x + 3)^2
Lastly we add/subtract the constant back to the right side.
y = (x + 3)^2 - 11